2009
DOI: 10.1007/s00376-009-8165-9
|View full text |Cite
|
Sign up to set email alerts
|

Possible causes for the persistence barrier of SSTA in the South China Sea and the vicinity of Indonesia

Abstract: The persistence barrier refers to the lag correlation of sea surface temperature anomalies (SSTA) showing a rapid and significant decline in a specific season, regardless of the starting month. This implies that there is a decrease in forecast skill for SSTA in this specific season. This paper investigates the possible causes for the persistence barrier of SSTA in the South China Sea (SCS) and its adjacent regions from the perspective of interannual-interdecadal time scales. The results show that the persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The above results confirm the existence of the SEIO SPB, SCS FPB, and SEIO WPB, which have been noted in previous studies (Wajsowicz 2005;Chen et al 2007;Luo et al 2007;Zhao and Li 2009). What causes the persistence barriers of the WIO, SCS, and SEIO SSTA during strong ENSO cases?…”
Section: Mechanisms Of Barrier Developmentsupporting
confidence: 91%
“…The above results confirm the existence of the SEIO SPB, SCS FPB, and SEIO WPB, which have been noted in previous studies (Wajsowicz 2005;Chen et al 2007;Luo et al 2007;Zhao and Li 2009). What causes the persistence barriers of the WIO, SCS, and SEIO SSTA during strong ENSO cases?…”
Section: Mechanisms Of Barrier Developmentsupporting
confidence: 91%
“…Similar to the phenomenon of autocorrelations of the tropical central–eastern Pacific SSTA, which show a rapid decrease in the boreal spring, Wajsowicz () reported that autocorrelations of the southeastern tropical Indian Ocean SSTA show a rapid decline in the boreal winter, resulting in a winter persistence barrier (WPB). Zhao and Li () also showed a similar persistence barrier of SSTA in the South China Sea and the vicinity of Indonesia around the southeastern tropical Indian Ocean. The WPB in the southeastern tropical Indian Ocean is associated with strong seasonal phase locking of the IOD.…”
Section: Seasonal Mean Predictability Limit Of Monthly Sstmentioning
confidence: 69%
“…Chen et al (2007) reported a fall persistence barrier (FPB) of the SSTA in the South China Sea (SCS), which is well recognized during the developing phase of strong ENSO cases but becomes vague in weak ENSO and non-ENSO cases. Zhao and Li (2009) showed that the persistence barrier of SSTA exists not only in the SCS but also in the vicinity of Indonesia. The SCS barrier occurs around October and November, while the barrier in the Indonesia region occurs around November and December.…”
Section: Introductionmentioning
confidence: 98%